2016
DOI: 10.1080/10376178.2016.1188018
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic symptoms and stressful working conditions among Palestinian nurses: a cross-sectional study

Abstract: Background: High levels of perceived stressful working conditions have been found to have an adverse effect on physical and mental health. Objectives: To examine the associations between self-reported stressful working conditions and Psychosomatic Symptoms (PSS), and to investigate possible gender differences. Methods: The present cross-sectional study comprises 430 nurses employed in Hebron district, Palestine. Self-reported stressful working conditions were recorded, and a Psychosomatic Symptoms Check list w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
(68 reference statements)
1
16
0
Order By: Relevance
“…Another study has shown that those who have tension-type headache tend to have anxiety and depression than those who do not have [27]. Jaradat et al have described that there was a significantly positive relationship between harsh work stress and tension-type headaches among nurses in both genders [28]. Not only tension-type headaches but also migraines are related to depression and anxiety [29] [30].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that those who have tension-type headache tend to have anxiety and depression than those who do not have [27]. Jaradat et al have described that there was a significantly positive relationship between harsh work stress and tension-type headaches among nurses in both genders [28]. Not only tension-type headaches but also migraines are related to depression and anxiety [29] [30].…”
Section: Discussionmentioning
confidence: 99%
“…The study was part of a larger study of Palestinian nurses employed at hospitals and primary health care clinics [4,7]. From October to December 2012, nurses were invited to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between WPA of any kind (no/yes) was larger than the overall difference between male and female nurses, which was 0.80. We had applied the same psychosomatic symptoms questionnaire in a previous study of psychosomatic symptoms and stressful working conditions among Palestinian nurses, where workplace aggression was not studied, and where the focus was to a large degree on work schedules and shift work . In that study we found that to work overtime increased the median psychosomatic symptom score from 11 to 12 for female nurses (adjusted 1.35) and from 9.5 to 10 for male nurses (adjusted 1.20) .…”
Section: Discussionmentioning
confidence: 91%
“…The population under study was Palestinian nurses employed in hospitals and primary health care clinics at the Hebron district. The study was part of a larger study of working conditions in Hebron District, Palestine …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation